The risky and protective motorcycling opinions and behaviours of young on-road motorcyclists in New Zealand - Reeder, A.I.; Chalmers, D.J.; Langley, J.D. (Social science & medicine (1982), 1996)
This research documented the frequency of protective and risky motorcycling opinions and behaviours and investigated whether these opinions and behaviours were more frequently expressed by licensed than unlicensed riders and by riders with high rather than low exposure to motorcycling. Areas where there was scope for improvement were identified to help guide the promotion of protective strategies. As part of a broader study of a birth cohort, 217 18 year old motorcyclists were administered a motorcycling computer questionnaire. Evidence of positive protective opinions was found, but there was considerable scope for behavioural improvements. While 92% had worn a helmet, optimal protection was reported less frequently for other body areas: most often for the feet (54%), hands (47%) and upper body (35%) and least often for the legs (8%). Most (87%) riders considered conspicuity increased safety, 68% favoured mandatory day-time headlight use, and 66% used dipped headlights in day-time. While 55% favoured mandatory wearing of high-visibility clothing, only 15% of day-time and 20% of night-time riders reported doing this. During the past month, 16% had driven within two hours of drinking alcohol and 6% when too tired to be fully in control. Overall, 22% had been penalized for a motorcycle driving offence, most often speeding. While 46% said they agreed with the Graduated Driver Licensing System (GDLS), most licensed under that system reported breaking licence conditions and most were not apprehended. Licensed motorcyclists were significantly more likely than the unlicensed to favour mandatory day-time headlight usage, report using dipped headlights in day-time, and wear better protection for the head, upper body and hands, but were also more likely to report drinking and driving and traffic convictions—probably because of their greater exposure. Other, non-significant, results were in the same direction, except that fewer licensed than unlicensed riders were in favour of mandatory high visibility clothing or the GDLS. A similar pattern of more protective attitudes and behaviours was found for high rather than low exposure riders, though it was generally weaker, and high exposure was associated with drinking and driving, driving while tired and traffic convictions. The issues of representativeness and reliability are discussed and some implications for public policies towards motorcycling by young people are considered. Further research is recommended in order to determine which are the best predictors of motorcycling opinions and behaviours: personal characteristics, the formal training associated with licensure, or exposure to motorcycling.